Queen conch (Strombus gigas) testis regresses during the reproductive season at nearshore sites in the Florida Keys. - Daniel J Spade; Robert J Griffitt; Li Liu; Nancy J Brown-Peterson; Kevin J Kroll; April Feswick; Robert A Glazer; David S Barber; Nancy D Denslow (PLoS ONE, 2010)
Background Queen conch (Strombus gigas) reproduction is inhibited in nearshore areas of the Florida Keys, relative to the offshore environment where conchs reproduce successfully. Nearshore reproductive failure is possibly a result of exposure to environmental factors, including heavy metals, which are likely to accumulate close to shore. Metals such as Cu and Zn are detrimental to reproduction in many mollusks. Methodology/principal findings Histology shows gonadal atrophy in nearshore conchs as compared to reproductively healthy offshore conchs. In order to determine molecular mechanisms leading to tissue changes and reproductive failure, a microarray was developed. A normalized cDNA library for queen conch was constructed and sequenced using the 454 Life Sciences GS-FLX pyrosequencer, producing 27,723 assembled contigs and 7,740 annotated transcript sequences. The resulting sequences were used to design the microarray. Microarray analysis of conch testis indicated differential regulation of 255 genes (p<0.01) in nearshore conch, relative to offshore. Changes in expression for three of four transcripts of interest were confirmed using real-time reverse transcription polymerase chain reaction. Gene Ontology enrichment analysis indicated changes in biological processes: respiratory chain (GO:0015992), spermatogenesis (GO:0007283), small GTPase-mediated signal transduction (GO:0007264), and others. Inductively coupled plasma-mass spectrometry analysis indicated that Zn and possibly Cu were elevated in some nearshore conch tissues. Conclusions/significance Congruence between testis histology and microarray data suggests that nearshore conch testes regress during the reproductive season, while offshore conch testes develop normally. Possible mechanisms underlying the testis regression observed in queen conch in the nearshore Florida Keys include a disruption of small GTPase (Ras)-mediated signaling in testis development. Additionally, elevated tissue levels of Cu (34.77 ng/mg in testis) and Zn (831.85 ng/mg in digestive gland, 83.96 ng/mg in testis) nearshore are similar to reported levels resulting in reproductive inhibition in other gastropods, indicating that these metals possibly contribute to NS conch reproductive failure.